Slaves and slave agency in the Ottoman Empire: with 10 figures - Conermann, Stephan; Şen, Gül (Ottoman studies, 2020)
Angaben zur beteiligten Person Conermann: Prof Dr Stephan Conermann teaches the History of the Islamicate World at the Institute of Oriental and Asian Studies, University of Bonn.
Keywords: Turkey; Aufsatzsammlung; Sklaverei; Osmanisches Reich; Geschichte 1300-1924